Renin–Angiotensin–Aldosterone System Inhibitors in Patients with COVID-19: General Considerations and Clinical Implications - Lima, Neiberg de Alcantara; Paiva Lima, Pedro Yuri; Castro Junior, Ricardo Lessa de; Sieloff, Eric Martin; Vitorino Sampaio, Stela Maria (JOURNAL OF CARDIAC ARRHYTHMIAS, 2020)
Initially reported in China at the end of 2019, the coronavirus pandemic has now reached an international scale with more than 1.5 million cases worldwide and more than eighty thousands deaths by April 8th of this year. Recent studies have shown that the virus invades host cells by the angiotensin-converting enzyme 2 receptor, making it essential to viral transmission. Concerns have been raised about possible benefits and harms associated with the use of ACE inhibitors and angiotensin receptors blockers in these patients. However, there is lack of evidence to recommend even temporarily discontinuing renin-angiotensin system inhibitors/blockers in patients infected with the SARS-CoV-2.